Reframing Physical Barrier Systems in Preventing Illegal Cross-Border Movement in the Kalimantan Border Region from Technical and Design Perspectives - Ni Wayan Sukreni (CV. Publikasi Indonesia, 2026)
The Indonesia–Malaysia land border in Kalimantan is a strategic area with a high vulnerability to illegal cross-border activities, particularly through unofficial routes known as jalan tikus (rat paths), which continue to increase in number. Border security efforts remain largely dependent on conventional patrols, which are constrained by limited personnel, difficult terrain, and insufficient infrastructure, resulting in suboptimal surveillance effectiveness. In this context, the Physical Barrier System (PBS) serves as a critical technical solution, functioning as a physical obstacle, an early detection mechanism, and a deterrent to prevent illegal border crossings. This study aims to analyse the technical and design aspects of PBS implementation in supporting the border security operations of the Indonesian National Armed Forces (Tentara Nasional Indonesia, TNI) using a qualitative-descriptive approach. Data were collected through literature review, analysis of operational and regulatory documents, and empirical reports from Border Security Battalions, and analysed using thematic categorization and source triangulation. The findings reveal that PBS deployment remains uneven and weakly integrated with sensor-based technologies, while its design has not yet fulfilled the principles of defense-in-depth, Crime Prevention Through Environmental Design (CPTED), and integrated access control. This study proposes an optimized PBS framework incorporating modular, terrain-adaptive design, intrusion detection sensors, early warning systems, structural reinforcement, and data integration with sector command posts.